2005
DOI: 10.1007/s00122-005-1941-8
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal location of a pollen fertility-restoring gene, Rf, for CMS in Japanese bunching onion (Allium fistulosum L.) possessing the cytoplasm of A. galanthum Kar. et Kir. revealed by genomic in situ hybridization

Abstract: In a previous study, we developed cytoplasmic male sterile lines of Allium fistulosum possessing the cytoplasm of A. galanthum, a wild species, by continuous backcrossing. Furthermore, we reported the presence of a pollen fertility-restoring gene (Rf) for cytoplasmic male sterility (CMS) in A. fistulosum from segregation of pollen fertility of backcross progenies. In the present study, genomic in situ hybridization (GISH), using genomic DNA of A. galanthum as the probe DNA and that of A. fistulosum as the bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Regarding bunching onion, molecular analyses of a fertility restoring gene have proceeded in CMS plants with A. galanthum cytoplasm. SCAR, RAPD and isozyme markers linked to the restoration locus (Rf) were developed (Yamashita et al 1999b(Yamashita et al , 2002, and the chromosomal location of the fertility restoration locus was determined to be 5F by the GISH method (Yamashita et al 2005). Recently, the detailed linkage map based on SSR markers was constructed in bunching onion (Tsukazaki et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding bunching onion, molecular analyses of a fertility restoring gene have proceeded in CMS plants with A. galanthum cytoplasm. SCAR, RAPD and isozyme markers linked to the restoration locus (Rf) were developed (Yamashita et al 1999b(Yamashita et al , 2002, and the chromosomal location of the fertility restoration locus was determined to be 5F by the GISH method (Yamashita et al 2005). Recently, the detailed linkage map based on SSR markers was constructed in bunching onion (Tsukazaki et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This CMS appears, however, not to have been agriculturally utilized due to its disease susceptibility. In previous reports, we introduced the cytoplasm of A. galanthum into bunching onion by continuous backcrossing and demonstrated that the cytoplasm could induce CMS in bunching onion (Yamashita et al 1999a(Yamashita et al , 1999b(Yamashita et al , 2002(Yamashita et al , 2005Yamashita and Tashiro 2004). This CMS was controlled by the cytoplasm of the wild species and a single fertility restoration locus (Rf) originating from the nuclear genome of A. galanthum.…”
Section: Introductionmentioning
confidence: 94%
“…In introgression breeding, discrimination of different genomes and chromosome locus identification is carried out by this method. Yamashita et al [19] applied the GISH technique to find out chromosome site of Rf (a restoring gene of pollen fertility) locus by comparing GISH results of male sterile and male fertile plants of introgressed progenies. To determine Rf locus location on chromosome, Allium galanthum genomic DNA was used as probe DNA, while for blocking DNA, Allium fistulosum genomic DNA was utilized for in situ hybridization of F 1 hybrids of both species and backcross generations.…”
Section: Chromosomal Evaluationmentioning
confidence: 99%
“…GISH analysis was conducted as described by Yamashita et al (2005) with some modifications. Total genomic DNA of C. schweinfurthii was extracted from young leaves according to the method of Doyle and Doyle (1987) with some modifications, labeled with biotin-16-dUTP using the Nick Translation Kit (Roche Diagnostics, Ltd., Rotkreuz, Switzerland), and used as the probe DNA; excess unlabeled genomic DNA of 'Nanpu' tangor was used as the blocking DNA.…”
Section: Gish-cma Analysismentioning
confidence: 99%